Complete Genome Sequences of Two T4-Like Escherichia coli Bacteriophages - Costa, Ana Rita (Genome Announc, 2018)
Bacteriophages and their proteins have potential applications in biotechnology for the detection and control of bacterial diseases. Here, we describe the sequencing and genome annotations of two strictly virulent Escherichia coli bacteriophages that may be explored for biocontrol strategies and to expand the understanding of phage-host interactions.